PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN FUNGSIONAL DI POLITKNIK NEGERI BATAM - Hati, Shinta Wahyu (JURNAL PERSPEKTIF BISNIS, 2013)
This study aims to determine the influence of environmental factors work terhadapa employee productivity. Environmental factors examined in this study is the coloring, cleanliness, ventilation, lighting, security and noise. The results showed that the factor is a variable coloration coloring dominant influence on the productivity of employees. Respondents are employees working in the functional part Polytechnic functional Batam.Karyawan are employees who work as educators. The results showed that the variables tested simultaneously proved exhibited significantly to productivity EmployeesÂ Keywords: work environment, productivity